(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: In India, despite of the fact that abortion facility is available legally under MTP act 1971, women seeking termination of pregnancy often ignore the legal status of abortions and have unsafe abortions. Medical abortion in the first trimester is safe, efficient and approved method of MTP, but should always be taken under the supervision of a registered medical practitioner. The unsupervised use of drug should be stopped as this can endanger life.Objective: To assess the effects of self-administered use of over the counter pill and compare it with the supervised use of mifepristone-misoprostol for medical termination of pregnancy in a tertiary care hospital; and to study its impact on women’s health.Methodology: The study was conducted in the Department of Obstetrics & Gynaecology at a tertiary care hospital of North India over one year period. 322 patients fulfilling the inclusion and exclusion criteria were taken up for the study. Data was compared and analysed in patients with history of self consumption of medical abortion pills versus supervised pills intake.Result: Majority of the patients were young, belonged to the urban area and were Hindu by religion (p<0.0001). Only 66.3% patients in the unsupervised group followed the correct regimen as compared to the supervised group where all the patients followed the correct regimen. The complication rate was 73.1% in unsupervised group as compared to 42.6% in supervised group (p<0.0001). There was significant statistical difference between both groups in respect to success and failure rate with p<0.0001.Conclusion: This study shows urgent need for legislation and restriction of drugs used for medical termination of pregnancy. Drugs should be made available via health care facilities under supervision to reduce maternal mortality and morbidity due to indiscriminate use of these pills.